Peripheral DNA methylation of HPA axis-related genes in humans: Cross-tissue convergence, two-year stability and behavioural and neural correlates. (November 2018) - Di Sante, Jessica; Ismaylova, Elmira; Nemoda, Zsofia; Gouin, Jean-Philippe; Yu, Wei-Jo; Caldwell, Warren; Vitaro, Frank; Szyf, Moshe; Tremblay, Richard E.; Booij, Linda
Highlights: Daily life stress is associated with HPA-axis related gene methylation. DNA methylation in HPA-axis genes is stable over time in healthy volunteers. DNA methylation-brain associations are gene and tissue specific. Measuring methylation in different tissues in the same persons can be recommended. Abstract: Environmental factors can influence gene expression via epigenetic modifications such as DNA methylation. DNA methylation levels of regulatory regions in Hypothalamo-Pituitary-Adrenal (HPA) axis-related genes assessed from brain tissues as well as from surrogate, peripheral tissues have been associated with vulnerability to stress-related psychopathologies. Commonly used peripheral samples to assess DNA methylation in living humans are derived from blood, saliva or buccal cells. Although psychiatric epigenetic studies are increasingly relying on peripheral measures of DNA methylation, it is still unknown to what extent methylation patterns across peripheral tissues are associated with each other and with measures of brain processes and behavioural stress. In the present study, with a sample of 51 healthy adults, we assessed cross-tissue correlations of DNA methylation patterns in the glucocorticoid receptor ( NR3C1 ) 1 F promoter and the FK506 Binding Protein 5 ( FKBP5 ) gene intron 7 region using saliva and buccal cell samples, and assessed two-year stability in both tissues in a male subsample (N = 14). We also investigated associations between peripherally-derived DNA methylation and measures of neural function and perceived daily stress, and compared the extent of these associations across tissue samples. DNA methylation cross-tissue correlations were highly significant for FKBP5, but not significant for NR3C1 . DNA methylation in both genes remained stable for two years. Tissue- and gene-specific associations were found for brain resting state connectivity and neural responses to sadness, thereby suggesting that saliva- and buccal cell-derived DNA methylation levels of NR3C1 -1 F and FKBP5 gene regions might differently capture different measures of putatively related brain processes. It was also found that greater buccal cell- (but not saliva-) derived NR3C1 -1 F methylation was associated with lower perceived daily life demands. Results of the present study may inform the design of future epigenetic studies on FKBP5 -intron-7 and NR3C1 -1 F-promoter methylation in relation to neuro-imaging and behavioural measures, and provide insight for the development of peripheral DNA methylation correlates of stress sensitivity and resilience.